NF-κB Signaling in Astrocytes Modulates Brain Inflammation and Neuronal Injury Following Sequential Exposure to Manganese and MPTP During Development and Aging. (21st July 2020) - Hammond, Sean L; Bantle, Collin M; Popichak, Katriana A; Wright, Katie A; Thompson, Delaney; Forero, Catalina; Kirkley, Kelly S; Damale, Pranav U; Chong, Edwin K P; Tjalkens, Ronald B
Abstract: Chronic exposure to manganese (Mn) is associated with neuroinflammation and extrapyramidal motor deficits resembling features of Parkinson's disease. Activation of astrocytes and microglia is implicated in neuronal injury from Mn but it is not known whether early life exposure to Mn may predispose glia to more severe inflammatory responses during aging. We therefore examined astrocyte nuclear factor kappa B (NF-κB) signaling in mediating innate immune inflammatory responses during multiple neurotoxic exposures spanning juvenile development into adulthood. MnCl2 was given in drinking water for 30-day postweaning to both wildtype mice and astrocyte-specific knockout (KO) mice lacking I kappa B kinase 2, the central upstream activator of NF-κB. Following juvenile exposure to Mn, mice were subsequently administered 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) at 4 months of age. Animals were evaluated for behavioral alterations and brain tissue was analyzed for catecholamine neurotransmitters. Stereological analysis of neuronal and glial cell counts from multiple brain regions indicated that juvenile exposure to Mn amplified glial activation and neuronal loss from MPTP exposure in the caudate-putamen and globus pallidus, as well as increased the severity of neurobehavioral deficits in open field activity assays. These alterations were prevented in astrocyte-specific I kappa B kinase 2 KO mice. Juvenile exposure to Mn increased the number of neurotoxic A1 astrocytes expressing C3 as well as the number of activated microglia in adult mice following MPTP challenge, both of which were inhibited in KO mice. These results demonstrate that exposure to Mn during juvenile development heightens the innate immune inflammatory response in glia during a subsequent neurotoxic challenge through NF-κB signaling in astrocytes.